2019
DOI: 10.3389/fneur.2019.00478
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Cycle Time Distinguishes Migraineurs From Subjects Without Headache

Abstract: Migraine is a neurological disorder characterized by paroxysms of head pain accompanied by trigeminovascular system activation and autonomic dysfunction. Diagnosis is currently based on clinical diagnostic criteria. Though physiological differences exist between migraineurs and non-headache controls, true physiological biomarkers have been elusive, especially for the full clinical spectrum of migraine, inclusive of chronic, episodic, and probable migraine. We used edge-light pupil cycle time (PCT) as a probe o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Prior studies of pupil response in migraine have obtained varying results. Prior studies have not found migraine group differences in the amplitude of pupil constriction or steady-state pupil size (57)(58)(59)(60), although more subtle changes in pupil dynamics have been reported (58,61,62). Our study differs from many prior reports in that we measured open-loop, consensual pupil responses by combining pharmacologic dilation with an artificial pupil, thus controlling retinal irradiance across the studied groups.…”
Section: Discussionmentioning
confidence: 80%
“…Prior studies of pupil response in migraine have obtained varying results. Prior studies have not found migraine group differences in the amplitude of pupil constriction or steady-state pupil size (57)(58)(59)(60), although more subtle changes in pupil dynamics have been reported (58,61,62). Our study differs from many prior reports in that we measured open-loop, consensual pupil responses by combining pharmacologic dilation with an artificial pupil, thus controlling retinal irradiance across the studied groups.…”
Section: Discussionmentioning
confidence: 80%
“…In another report, increased pupil cycle time in probable, episodic, and chronic migraine was associated with mixed hypofunction of both sympathetic and parasympathetic innervation. 11 On the other hand, in the study of Koban et al there was no difference in pupil size measured during the ictal and interictal period in migraine patients. They also found no difference between migraine patients and controls.…”
Section: Discussionmentioning
confidence: 85%
“…[6][7][8] Although previous studies reported sympathetically Effect of migraine attack on pupil size, accommodation and ocular aberrations mediated pupillary dysfunction in patients with migraine, some studies suggested mixed parasympathetic and sympathetic dysfunction. [9][10][11] The autonomic nervous system regulates many ocular functions, such as pupil reflexes, accommodation, ocular blood flow, and intraocular pressure. Accommodation is a natural adaptive optical mechanism for improving the retinal image of a nearby object.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cardiac vagal responses via baroreceptors are reduced in migraine patients, but sympathetic system-related responses are not. As a consequence, it appears that the autonomic nervous system may play a role in the pathophysiology of migraine [21]. The pupillary hippus phenomenon can be extinguished with antagonists of the parasympathetic nervous system, whereas antagonists of the sympathetic system dilate the pupils without blocking the hippus: this suggests that the phenomenon originates in the centrally localized parasympathetic system and not in the sympathetic system [10].…”
Section: Discussionmentioning
confidence: 99%